Turnover intention in Non-Governmental Organisation (NGOs): a case study of recreation society at Kuantan, Pahang / Mazlan Mamat and Wan Asri Wan Ab. Aziz - Mamat, Mazlan; Wan Ab. Aziz, Wan Asri (2021)
The hidden cost caused by employee turnover is inevitable. In filling in the vacancy of a position, the causes of turnover will affect the cycling systems. Low turnover rate is essential to an organization's human resources department as it shows an excellent indicator of budgeting and training cost. This study aims to examine the significant relationship between the factors namely organizational commitment, job stress, job satisfaction and reward satisfaction with turnover intention among committee members in recreation society at Kuantan, Pahang. The sample size of respondents from this society selected in Kuantan, Pahang is 169 from 316 of the population sizes. Stratified random sampling technique was chosen in achieving the objectives of this study because it is a systematic data collection method. The data for this study was collected from the questionnaires distributed to the respondents by using Google form. Altogether, there are four independent variables and one dependent variable. Statistical Package for Social Science version 23 (SPSS) was employed to perform data analysis of the study. The study discovered that organizational commitment, job stress, job satisfaction, and reward satisfaction have significant relationships with turnover intention. These factors like organizational commitment, job stress, job satisfaction and reward Satisfaction are suitable in predicting and analysing organizational behaviour regarding human resource management. Hence, it is crucial to study turnover intentions in organizational management.